2023
DOI: 10.3389/fonc.2023.1242453
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory neuroblastoma: diagnosis, management, and current treatment options

Alicia Tosoni,
Vincenzo Di Nunno,
Lidia Gatto
et al.

Abstract: Olfactory neuroblastoma (ONB) is a rare neoplasm originating from the olfactory neuroepithelium representing 3-6% of tumors of the sinonasal tract. ONB require multi-disciplinary care. Historically, the gold standard surgical procedure for ONB has been open craniofacial resection. In the last years, endoscopic endonasal approaches have been largely introduced with lower complication rates, shorter hospital stay, and similar clinical outcome. Radiotherapy plays an important role in the management of ONB, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Various retrospective studies and two metaanalyses demonstrated that a combined treatment improves the survival outcomes, especially in advanced stages [11][12][13][18][19][20]. Open craniofacial resection used to be the gold standard surgical procedure, although, in the last years, endoscopic endonasal approaches have been preferred, mainly in the early stages [21]. Regarding RT, the literature recommends preoperative doses of 45 Gy and postoperative doses of 50 to 60 Gy, according to surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…Various retrospective studies and two metaanalyses demonstrated that a combined treatment improves the survival outcomes, especially in advanced stages [11][12][13][18][19][20]. Open craniofacial resection used to be the gold standard surgical procedure, although, in the last years, endoscopic endonasal approaches have been preferred, mainly in the early stages [21]. Regarding RT, the literature recommends preoperative doses of 45 Gy and postoperative doses of 50 to 60 Gy, according to surgical margins.…”
Section: Discussionmentioning
confidence: 99%